9514 1404 393
Answer:
f(x) = x² +3
Explanation:
The transformation
g(x) = a·f((x -c)/b) +d
represents a vertical expansion by a factor of 'a', a horizontal expansion by a factor of 'b' (before the horizontal shift), a horizontal (right) shift by 'c' units, and an upward shift by 'd' units.
You want only an upward shift of 3, so ...
g(x) = f(x) +3
For f(x) = x^2, the shifted function is ...
f(x) = x^2 +3
__
Other choices are ...
b. (x -3)^2 = right shift by 3
c. 3x^2 = vertical expansion by a factor of 3
d. (x +3)^2 = left shift by 3